Assessment of grid/filter size dependence in large eddy simulation of high-pressure spray flames. (1st December 2022) - Zhong, Shenghui; Xu, Leilei; Xu, Shijie; Zhang, Yan; Zhang, Fan; Jiao, Kui; Peng, Zhijun; Bai, Xue-Song
Abstract: With the increase of computing power, large eddy simulation (LES) within the Lagrangian–Eulerian two-phase flow framework has evolved as an useful numerical tool to gain insights to the spray combustion processes in advanced internal combustion engines. However, the inherent effect of grid/filter size (G/FS) on the physics revealed by LES is not fully understood. In this paper, we present several new viewpoints on this by analyzing the results from a Lagrangian–Eulerian LES study of Engine Combustion Networks Spray A with a newly developed multi-region adaptive mesh refinement method in OpenFOAM. It is found that G/FS affects the predicted spray characteristics, the modes of spray combustion, the ignition delay time and the liftoff length in different ways. First, owing to the nature of Lagrangian particle-in-cell approach, the spray liquid penetration length converges as the G/FS approaches to the nozzle diameter. The convergence behavior is rather independent of the spray model parameters. Second, it is critical to have a well resolved spray liquid region; the main spray combustion characteristics, e.g., the mean pressure rise profile, the onsets of the cool flame and hot flame, and the main flame structure, are shown to be similar and independent of G/FS once the liquid region is properly resolved. However, the detailed flame structures at the liftoff position are sensitive to G/FS; the upstream auto-ignition events, the low temperature ignition assisted flame propagation and the hot flame propagation, are shown to partially rely on the adopted G/FS. Finally, it is found that a finer G/FS predicts a slower fuel/oxidizer mixing and a shorter flame liftoff length, yielding a higher soot mass. Highlights: We proposed a novel multi-region adaptive mesh refinement (AMR) method for ECN Spray A flames. Using the multi-region AMR method can obviously improve the grid size convergence of flame characteristics. The spray ignition position and timing are insensitive to the grid size employed (from 250 μ m to 62 . 5 μ m ). The flame liftoff and soot formation are closely related to the grid size employed. More fruitful combustion modes at flame liftoff position are captured with finer grid size.